South African restaurant reviewing: a changing landscape? - Stiehler-van der Westhuiz, Adele (University of the Witwatersrand, Johannesburg, 2024)
This study investigates the changes that have taken place in the South African restaurant reviewing landscape between 2000 and 2020. Changes in society’s relationship with food, together with a changing media landscape and the end of apartheid, have combined to create a colourful cocktail of cultural changes in South Africa, which is currently academically underexplored. A historical methodology was followed to track these changes and included the compilation of an archive of 426 reviews published about three restaurants chosen from Eat Out magazine’s 20th-anniversary issue. Through a close reading and content analysis of the archive and by drawing on public sphere and cultural consecration theories the study found that the food reviewing field was neither inclusive, not particularly professional if measured by the guidelines set out by the legendary New York Times reviewer, Craig Claiborne, and that there were two distinct decades in the archive. The first was dominated by positive reviews in traditional media written mainly by professional reviewers. The second decade represented the “democratisation” of online reviewing with a significant increase in reviews (positive and negative) written mainly by amateurs on rating sites. The fact that white females dominated the reviewing space throughout the 20 years under study is evidence of the legacy of apartheid and confirms that privilege and power still shaped the foodscape. This study also tracked the tensions between players in the restaurant reviewing field and confirmed that amateur reviewers did not reject culinary capital but rather reinforced it, and professional reviewers embraced rather than avoided the digital media platforms. Amateur reviewers applied different reviewing criteria and wrote consumer assessments focused on lived experiences, rather than cultural assessments, like many professional reviewers. This study therefore suggests that their reviews are complementary to professional reviews, not competing. The arrival of Web 2.0 and mobile phones also changed the form of reviews radically during the 20 years, with commenting and sharing functionalities turning some reviews into vibrant conversations and photographs and videos becoming the new way to review.
A research report submitted in fulfillment of the requirements for the degree of Master of Arts by Dissertation in Journalism and Media Studies to the to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Restaurant Reviewing; Food Writing; Critics; SDG-9: Industry, innovation and infrastructure